A new generalized exponential rational function method to find exact special solutions for the resonance nonlinear Schrodinger equation - Ghanbari, Behzad; İnç, Mustafa (Springer Heidelberg, 2018)
The present paper suggests a novel technique to acquire exact solutions of nonlinear partial differential equations. The main idea of the method is to generalize the exponential rational function method. In order to examine the ability of the method, we consider the resonant nonlinear Schrodinger equation (R-NLSE). Many variants of exact soliton solutions for the equation are derived by the proposed method. Physical interpretations of some obtained solutions is also included. One can easily conclude that the new proposed method is very efficient and finds the exact solutions of the equation in a relatively easy way.
Keywords: Law Nonlinearity; Solitons; Bright